Visual Scaffolding through the Picture-and-Picture Strategy: Evidence from a Quasi-Experimental Study of Arabic Writing Instruction - Rosheila Melani; Mustar; Yogia Prihartini; Muhammad Kumaini Umasugi; Mohamad Sarip; Abdul Hakimi Abdurrahman Hussein (Al-Muyassar: Journal of Arabic Education, 2026)
Arabic writing skill (maharah al-kitabah) remains a challenge for madrasah students due to limited vocabulary mastery and difficulties in organizing ideas into coherent texts. This study aims to examine the effect of the Picture and Picture strategy on improving Arabic writing skills among ninth-grade students at MTs Nurul Iman Ulu Gedong, Jambi. This research employed a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design involving 30 students divided into experimental and control groups. Data were collected through writing tests administered as pre-test and post-test and analyzed using paired samples t-test and independent samples t-test. The results showed that both groups experienced significant improvement; however, the experimental group achieved higher improvement with a mean difference of 23.27 (t(14) = -14.530, p < 0.001) compared to the control group with a mean difference of 10.57 (t(14) = -6.764, p < 0.001). The independent samples t-test confirmed a significant difference between the two groups (t(28) = 7.586, p < 0.001). The novelty of this study lies in revealing that Picture and Picture functions as visual scaffolding that supports students in organizing ideas, developing vocabulary, and constructing Arabic sentences systematically. This study theoretically strengthens visual-based approaches in Arabic language learning and practically provides an alternative strategy for teachers to improve students’ writing competence.